Students’ Technique in Translating English Text (Learning Sources For English Education Study Program Students) - Ika Paramitha Lantu; Defrianto Nesika (Sintuwu Maroso Journal of English Teaching, 2020)
This study aims to analyze students' techniques in translating English text in the form of argumentative text at Sintuwu Maroso University. The research objects were 24 of sixth semester students of English Department. This research is a qualitative descriptive one that collected data through test (a Translation test) which was given to the students. The test results were analyzed by using the theory of target language text by Molina and Albir about Translation Technique. The results of this study indicated that in translating English-language text into Indonesia, the students use literal translation, borrowing, modulation, reduction, and established equivalent.